Eye for an eye - Field, Sally; Sutherland, Kiefer; Harris, Ed, 1950-; Paramount Pictures, inc. (Hollywood, Calif. ; Paramount, 1996)
Karen McCann's orderly life is shattered when a stranger breaks into her home and murders her 17-year-old daughter. But shock and grief turn into rage and disbelief when the killer is released on a legal technicality. When he commits another murder--and is set free once again-- Karen is determined to make him pay for his crimes. Alienating her husband and her friends, Karen quietly and methodically devises a deadly plan for retribution.
Originally released as a motion picture.
Sally Field, Kiefer Sutherland, Ed Harris, Beverly D'Angelo, Joe Mantegna.
Closed-captioned for the hearing impaired.
Rated R.
DVD.
Keywords: Video recordings for the hearing impaired; Feature films; Suspense films